Maximizing the Efficacy of Soil Fumigant Applications for Raised-Bed Plasticulture Systems of Florida - Andrew MacRae; Joseph Noling; Crystal Snodgrass (EDIS, 2010)
HS1169, a 5-page fact sheet by Andrew MacRae, Joseph Noling, and Crystal Snodgrass, describes several factors in crop production that should be considered to maximize the efficacy of alternatives to methyl bromide. Published by the UF Department of Horticultural Sciences, April 2010.